Trends in the prevalence of kidney stones in the United States from 2007 to 2016 - Chewcharat, Api; Curhan, Gary (Urolithiasis, 2021)
The overall prevalence of kidney stones (KS) in the US rose from 3.2% in 1980 to 10.1% in 2016, but the trends in important subgroups have not been reported. We examined the prevalence trends of KS in subgroups of age, sex and race in the US and identified relevant laboratory factors associated with a history of KS using National Health and Nutrition Examination Survey (NHANES) data. We conducted a cross-sectional study among 28,209 US adults aged ≥ 20 years old in the NHANES from 2007 to 2016. We calculated the prevalence of a self-reported history of KS by using weights and standardized to the 2010 US Census population. We also compared relevant laboratory values according to the history of KS. The prevalence of KS decreased from 8.7% in 2007–2008 to 7.2% in 2011–2012 but then increased to 9.0% in 2013–2014 and 10.1% in 2015–2016. However, the overall prevalence of KS increased over 2007–2016 ( p -trend = 0.02). Prevalence of KS among men was higher than women. Among men aged 20–79, there were significant quadratic trends in the prevalence of KS. Whereas, the prevalence of KS increased as a linear trend among women aged 20–59 years over 2007–2016. There were no consistent trends in the prevalence of KS by race. The prevalence trend of KS among non-Hispanic whites was 9.8% from 2007 to 2010 then dropped to 7.9% in 2011–2012 and increased to 10.6% in 2013–2014 and 12.1% in 2015–2016. A similar trend was also observed among non-Hispanic blacks. Among Hispanic, the prevalence of KS was 7.6% in 2007–2008 and 7.4% in 2009–2010 and then fluctuated over the next several time periods. For non-Hispanic Asians, the range was 4.4–4.6%. Regarding relevant laboratory factors, after adjusting for sex, race, age, BMI, smoking status, alcohol drinking, history of diabetes and gout, urine albumin-creatinine ratio and serum osmolality were independently associated with the history of KS in women and men. In conclusion, there was substantial variability in KS prevalence across individual 2-year time periods. This variation of period-specific prevalence values emphasizes the importance of looking at long-term trends and using more than a single 2-year cycle in analyses to increase the precision of the estimate. However, there was an overall increase in the prevalence of KS over 2007-2016.